Spatial distribution of a multidimensional urban poverty index in Metropolitan Lima - Ordóñez Mercado, Alipio Francisco (2015)
An exploratory analysis of the spatial distribution of social indicators in developing countries is essential to understand how these indicators are distributed geographically. Particularly in this study we intend to describe the spatial distribution of the multidimensional poverty index across the districts of Metropolitan Lima by crossing its borders and establishing a certain degree of competitiveness among local governments, so that their authorities take corrective action policies and strengthen the level of key indicators on which the corresponding social index depends. The new ingredient in this type of studies is the consideration of the geographical coordinate of each of the districts in the analysis, so that the methodological design takes into account not only the occurrence of the phenomenon of interest, but also its geographical location and its possible interaction in space.